2023
DOI: 10.3389/fenvs.2023.1071353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heavy metal contamination of soil and the health risks in four potato-producing areas

Abstract: Areas polluted by heavy metals in soil may pose a major risk to human health and ecological environment safety. In this study, 89 soil samples were collected from four potato producing areas (Libo, Chishui, Panxian and Weining) in Guizhou Province, China, and the concentrations of 9 soil heavy metals were analyzed and measured. The aims of this study was to evaluate the human health risk and pollution index of heavy metals in the soil of some potato-producing areas in Guizhou Province by using the geoaccumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In their study, the naturally contaminated soil samples were found to have concentrations lower than the maximum permissible limits established by the European Union [ 41 ]. The metal values were much higher in the spiked soils, as these concentrations are hardly found in real life, even in mines, and would be a significant risk to people’s health [ 30 , 44 , 45 ]. However, the presented concentrations were selected to meet the requirements of investigating the limitations of the quantitative determination of metals using certain analytical techniques.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, the naturally contaminated soil samples were found to have concentrations lower than the maximum permissible limits established by the European Union [ 41 ]. The metal values were much higher in the spiked soils, as these concentrations are hardly found in real life, even in mines, and would be a significant risk to people’s health [ 30 , 44 , 45 ]. However, the presented concentrations were selected to meet the requirements of investigating the limitations of the quantitative determination of metals using certain analytical techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The soil samples of the study which were naturally contaminated, were found to have concentrations lower than the maximum permissible limits established by the European Union [39]. The metal values were much higher in the spiked soils, as these concentrations are hardly found in the real life, even in mines, and would be a significant risk to people's health [30,42,43]. Ηowever, the presented concentrations were selected to meet the requirements of the investigation into the limitations of metals' quantitative determination using certain analytical techniques.…”
Section: Physico-chemical Features Of Soil Samplesmentioning
confidence: 99%
“…Metals and metalloids are naturally available in the soil system, but careless human activities like unplanned effluent management and long-term irrigation with contaminated wastewaters are bound to fill up the trace metal bearing capacity of the soil, after which these trace elements find their way towards contaminating groundwater, surface water and eventually the plants and crops [ 53 , 54 ]. As the most popular vegetable, high trace metal accumulation in potatoes would pose a greater health risk because food chain contamination is one of the major routes for trace metals' entry into the human body [ 23 , 33 , 55 ]. The massive population of Bangladesh creates a huge food demand resulting in mostly year-round cultivation of available arable lands.…”
Section: Introductionmentioning
confidence: 99%